Atomically Thin Two-Dimensional Kagome Flat Band on the Silicon Surface - Lee, Jae Hyuck; Kim, Gwan Woo; Song, Inkyung; Kim, Yejin; Lee, Yeonjae; Yoo, Sung Jong; Cho, Deok Yong; Rhim, Jun Won; Jung, Jongkeun; Kim, Gunn; Kim, Changyoung (ACS Nano, 2024)
In condensed matter physics, the Kagome lattice and its inherent flat bands have attracted considerable attention for their prediction and observation to host a variety of exotic physical phenomena. Despite extensive efforts to fabricate thin films of Kagome materials aimed at modulating flat bands through electrostatic gating or strain manipulation, progress has been limited. Here, we report the observation of a d-orbital hybridized Kagome-derived flat band in Ag/Si(111) Formula Presented as revealed by angle-resolved photoemission spectroscopy. Our findings indicate that silver atoms on a silicon substrate form an unconventional distorted breathing Kagome structure, where a delicate balance in the hopping parameters of the in-plane d-orbitals leads to destructive interference, resulting in double flat bands. The exact quantum destructive interference mechanism that forms the flat band is uncovered in a rigorous manner that has not been described before. These results illuminate the potential for integrating metal-semiconductor interfaces on semiconductor surfaces into Kagome physics, particularly in exploring the flat bands of ideal 2D Kagome systems.
Keywords: ARPES; Condensed-matter physics; D orbitals; Destructive interference; DFT; Flat band; Kagome; Kagome lattice; Silicon surfaces; Two-dimensional; ARPES; d-orbital; DFT; flat bands; Kagome; silicon; two-dimensional